Reconstruction of alveolar cleft with allogenous bone graft: clinical considerations - Omar Gabriel da Silva Filho; Terumi Okada Ozawa; Cláudia Bachega; Marco Aurélio Bachega (Dental Press Editora, 2013)
INTRODUCTION: Secondary bone grafting consists in a routine procedure on the treatment of patients with alveolar cleft. Usually, it is performed by the end of the mixed dentition, when the permanent canine is erupting, with autogenous cancellous bone from the iliac crest. OBJECTIVE: The present article discusses the alternative of autogenous bone grafting with allogeneic bone, obtained from human bone bank, illustrating the result with the presentation of a clinical case of left unilateral alveolar cleft.